2011
DOI: 10.1091/mbc.e11-05-0469
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor adenomatous polyposis coli controls the direction in which a cell extrudes from an epithelium

Abstract: Adenomatous polyposis coli (APC) controls the direction in which cells extrude from epithelia. APC acts in the dying cell to control where microtubules target actomyosin contraction in neighboring cells that squeeze out the dying cell. APC mutations that frequently occur in colon cancer cause cells to extrude aberrantly beneath epithelia, which could enable tumor cell invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 24 publications
(47 reference statements)
4
92
0
Order By: Relevance
“…This localized contraction enables apical constriction during invagination [73] or defines the topography of cell extrusion (apical or basal side of the epithelial monolayer). At the molecular level, cell extrusion directionality is driven by specific oncogenes (Ras, APC) [74,75] and the engagement of N-WASP or crosslinking proteins such as filamins or EPLIN [45,76,77].…”
Section: Thin Bundles and The Regulation Of Lateral Height And Junctimentioning
confidence: 99%
“…This localized contraction enables apical constriction during invagination [73] or defines the topography of cell extrusion (apical or basal side of the epithelial monolayer). At the molecular level, cell extrusion directionality is driven by specific oncogenes (Ras, APC) [74,75] and the engagement of N-WASP or crosslinking proteins such as filamins or EPLIN [45,76,77].…”
Section: Thin Bundles and The Regulation Of Lateral Height And Junctimentioning
confidence: 99%
“…For instance, the binding of APC to itself via N-terminal and C-terminal domains affects its interaction with proteins that bind to the armadillo region (Li and Näthke, 2005). Heterozygous expression of such truncated fragments causes measurable changes in cell migration, and changes the ability of cells to extrude from epithelial tissue normally during homeostasis (Marshall et al, 2011;Nelson et al, 2012). However, the detailed molecular mechanisms that underpin these changes are not known.…”
Section: Regions Of Apc Involved In Proteinprotein Interactionsmentioning
confidence: 99%
“…Similarly, the contribution of APC to the regulation of cytoskeletal proteins, particularly microtubules and actin, is well established (Moseley et al, 2007;Munemitsu et al, 1994;Näthke et al, 1996;Okada et al, 2010;Smith et al, 1994). The changes in cytoskeletal organization and processes associated with microtubules and actin, including migration and cell division that accompany APC loss, have been described by many research groups (Caldwell et al, 2007;Dikovskaya et al, 2010;Dikovskaya et al, 2004;Dikovskaya et al, 2007;Green et al, 2005;Green and Kaplan, 2003;Kita et al, 2006;Kroboth et al, 2007;Marshall et al, 2011). In the context of cancer, changes in these interactions of APC cause cells to migrate less efficiently and to increase their residence time in the challenging environment of the intestinal tract (Nelson (See poster insert) et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our Gal4 enhancer trap lines can be used to manipulate gene expression within specific epithelial cell types, as well as follow their movements and behaviors under physiological conditions and during pathogenesis or carcinogenesis. Recent studies have demonstrated that mutations in conserved tumor suppressor genes or the sphingosine-1-phosphate signaling pathway lead to altered epithelial cell behaviors and hallmarks seen in aggressive tumors (Gu et al, 2015;Marshall et al, 2011;Reischauer et al, 2009), highlighting the utility of the zebrafish epidermis to model the earliest events of carcinoma formation and progression. Our toolset now provides new strategies for loss-of-function studies for the zebrafish epidermis (Fig.…”
Section: Discussionmentioning
confidence: 99%